The Red Sports Culture is Integrated Into The Public Sports Curriculum of Colleges And Universities Evaluation System Construction And Path Analysis - Zhang, Lei; Huang, Jin; Wang, Shaojie; Jiang, Bo (Quality in Sport, 2024)
The red sports culture, which was born in the revolutionary era, is an excellent traditional culture of the Chinese nation. Its inheritance and development reflects the theoretical consciousness of the coordinated development of "cultural power" and "sports power". The integration of red sports culture into the public physical education curriculum of colleges and universities is the in-depth analysis of the concept of cultivating college students' "cultural self-confidence" and the goal path of forging ahead "sports power". In this study, the literature method, Delphi method, expert interview method, analytic hierarchy process and other research methods are used to construct the evaluation system of integrating red sports culture into public physical education courses in colleges and universities, including 4 first-level indicators, 13 second-level indicators and 42 third-level indicators, and determine the weights of indicators at all levels. Finally, objective analysis and case enumerations are made according to the weights assigned to indicators at all levels. And put forward the path of integrating red sports culture into college public physical education curriculum construction.